INTEGRATIVE METHODOLOGICAL SYSTEM FOR IMPROVING THE PROCESS OF KINESTETIC DEVELOPMENT IN PREPARING STUDENTS FOR PROFESSIONAL ACTIVITY IN THE CONTEXT OF GLOBALISATION AND DIGITAL EDUCATION. (Universal International Scientific Journal, 2026)
This article discusses the issues of improving kinesthetic development in the process of preparing students for professional activity in a globalization and digital educational environment. The study analyzes the role of family psychology, gender stereotypes, mental health, and pedagogical erudition based on an integrative approach. A methodological system is justified to improve the quality of education and the effectiveness of professional training through the development of kinesthetic competencies.
Keywords: kinesthetic development, professional training, digital education, mental health, pedagogical erudition, methodological system